THE RELIGIOUS AND CULTURAL FACTOR IN TURKEY’S POLICY REGARDING THE BALKANS AT THE NEW STAGE OF RELATIONS (2016–2020) (Південний архів (історичні науки), 2024)
The purpose of the work is to analyze the cultural and religious influence of Turkey on the territory of the Balkan region in the period from 2016 to 2020. The research methods that were used: the method of deduction (the author first studied the picture of general trends in the Balkan region, and only then analyzed in detail their features in individual countries) and induction (everything was summarized in the conclusions), methods of analysis and synthesis (the analysis was used in the main part of the text, and the synthesis is mainly in the conclusions), content analysis (exactly what leading political figures said in their speeches was analyzed), from specifically historical ones – comparativehistorical (religious and cultural influence was analyzed synchronously in different countries), as well as the method hermeneutics in working with sources. Results: it was found out by what methods and with what intensity the religious and cultural influence of Turkey was carried out in various countries of the Balkan region; it was revealed which countries belonged to the primary interests of Ankara, and which countries were secondary; the activity of the main institutions and organizations through which influence was exercised was analyzed; the motivational aspect of Turkey’s geopolitical actions in the Balkans is followed, both obvious and hidden. Conclusions. It was revealed that at a new stage of its political development, Ankara began to pay more attention to countries that were beneficial for it from a pragmatic point of view, that is, those in which it is profitable to invest. In countries such as Albania, Bosnia and Herzegovina, Kosovo during this period, cultural and religious influence is mainly concentrated (restoration of mosques and in some places Christian shrines, increase of cultural projects, for example, from the Yunus Emre Institute, popularization of Turkish education through the Maarif fund, etc.). The emphasis was on protecting the interests of Muslims around the world and opposing European “islamophobia”. These were important and useful steps for the development of countries, but both politicians and ordinary citizens often criticized Turkey. The funds that Ankara invested in this group of Balkan countries were insignificant compared to those invested in projects and cooperation with economic partners.
Keywords: Turkey, Balkan region, R.T. Erdogan, “erdoganism”, “soft power”, Ummah, mechanism of influence.